Legislation on German Colonies Near St. Petersburg in 18th — Early 19th Centuries (Complete Collection of Laws of Russian Empire) - I. V. Cherkasyanova (Научный диалог, 2023)
The article is devoted to the analysis of laws about German colonies near St. Petersburg, published in the Complete Collection of Laws of the Russian Empire. The documents from 1763 to 1803 are studied. The relevance of the work is determined by the state of historiography on Russian Germans in the Northwest. A review and analysis of the texts of laws are carried out, historical information contained in the texts is analyzed, missing documents that were used in practice are identified. The names of officials mentioned in the laws are revealed. It is stated that the corpus of laws for research is divided into acts related to all foreign colonists in Russia and acts regulating the life of St. Petersburg colonies. It is noted that laws related to suburban colonies are divided into two groups: documents of “northern” colonies founded in the 18th century and “coastal” colonies that emerged in the first decade of the 19th century. Laws about “northern” colonies are considered, which relate to the admission and placement of colonists, their internal structure, economic development, size of land grants, state debt, and its repayment. It is established that from the end of the 18th century, the topic of colonists leaving for the city and forming a layer of craftsmen and merchants from among them arises. German colonies; St. Petersburg colonists; legislation; Complete Collection of Laws of the Russian Empire; St. Petersburg; Tsarskoe Selo; Oranienbaum; patrimonial and state lands.